Influence of Nitric acid and RE-OA-H3PO4 acid solution on formation of porous anodic aluminium oxide (AAO) thin film - Juyana A. Wahab (Universiti Malaysia Perlis, 2008)
Anodizing is very suitable process in formation of porous AAO thin film. By controlling the anodizing parameters such as voltage, time, temperature and acid solution during the anodizing process, a layer of AAO thin film with porous microstructure can be formed. In this study, aluminium foils were anodized in different acid solutions which are HNO3 and Re-OA-H3PO4 by varying the anodizing parameters. The anodized samples then were characterized by using SEM, EDX and XRD techniques. The results showed that higher voltages and long anodizing time resulted to the larger pores sizes. The anodizing voltage around 90 – 110 V produced the pores size in the range of 70 - 100 nm. Besides, the anodizing time around 40 minutes produced the pore size in the range of 80 – 100 nm. The increasing of acid concentration also led to the formation of Al2O3 films with lower porosity. The purpose of this research is to show how the voltage, acid solution and anodizing time influence the formation of porous AAO thin film on the aluminium foil surface.